Responsible Use of Artificial Intelligence in International Marketing: A Comparative Analysis of Multinational Enterprises - Lager, Mia-Kristina; Hasan, Rakibul; Ojala, Arto; Li, Yanwen (Springer, 2026)
This chapter examines how leading multinational enterprises (MNEs) are integrating responsible artificial intelligence (AI) practices into their international marketing (IM) strategies. Although there is significant discourse on AI ethics, its specific application within IM still needs to be explored. Our study examines how MNEs communicate their responsible use of AI in international marketing and explores the extent to which this communication aligns with the AI principles set by the OECD. We analyze the ethical guidelines of the eight leading MNEs listed in the Fortune Global 500, evaluating the comprehensiveness of their AI-driven marketing practices against OECD’s AI Principle. These principles promote innovation, trustworthiness, respect for human rights, and democratic values. By comparing MNEs’ practices against global ethical frameworks, we provide insights into the current state of AI ethics in international marketing. Additionally, the research proposes new avenues for further studies on the topic.
Keywords: Responsible artificial intelligence; AI ethics; International marketing; Multinational enterprises (MNEs); OECD AI principles; AI-driven marketing; fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Kansainvälinen liiketoiminta|en=International Business|; fi=Kansainvälinen liiketoiminta|en=International Business|